Multiple intelligences in the classroom - Armstrong, Thomas; Association for Supervision and Curriculum Development (Alexandria, Va. : Association for Supervision and Curriculum Development, 2000)
Explains the theory of multiple intelligences developed by Howard Gardner in which he maps a broad range of human abilities by grouping them into seven categories; and discusses how the theory can be applied to issues of classroom teaching, especially with students who have been classified as learning disabled.
The foundations of the theory of multiple intelligences -- MI and personal development -- Describing intelligences in students -- Teaching students about MI theory -- MI and curriculum development -- MI and teaching strategies -- MI and the classroom environment -- MI and classroom management -- The MI school -- MI and assessment -- MI and special education -- MI and cognitive skills -- Other applications of MI theory -- MI and existential intelligence.
Includes bibliographical references (p. 141-144) and index.
"ASCD stock no. 100041"--T.p. verso.
Keywords: Teaching; Cognitive styles; Learning; Multiple intelligences; Intelligences multiples; Teaching; Cognitive styles; Learning